The Influence of Low Self-Control and Thoughtfully Reflective Decision Making on Criminal Justice Processing - Boccio, Cashen (American journal of criminal justice, 2022)
Previous research indicates that individual-level factors, such as low self-control, are related to criminal involvement (Pratt & Cullen, 2000). Comparatively less research, however, has examined whether individual-level factors may also influence the likelihood of being apprehended for criminal behavior. This study addresses this gap in the literature by examining the influence of levels of self-control and thoughtfully reflective decision making (TRDM) on being processed by the criminal justice system. Our results reveal that low self-control, but not TRDM, is associated with number of arrests after controlling for criminal involvement. We discuss the implications of these findings for future research and the existing literature.